Optimal location selection for a new processing plant using supply chain and distribution network analysis - Musa, Adekunle Ibrahim (Journal Industrial Servicess, 2025)
Selecting an optimal processing plant location is a critical decision in supply chain management, directly affecting operational efficiency, cost-effectiveness, and distribution logistics. This study aims to identify the most suitable location for a new processing plant that sources raw materials from three suppliers and distributes finished products to two distribution points. We employed the Center-of-Gravity method to determine the optimal geographical location and a cost-minimization model to ensure minimal transportation expenses. We analyzed data on supply capacities, demand requirements, transportation costs, and geographical coordinates. The Center-of-Gravity calculations identified an optimal location at coordinates (24.67, 19.50). Further cost-optimization modeling revealed that this location reduces total transportation costs to NGN 80,500.00, yielding lower costs than alternative sites. These findings confirm that an optimally selected plant location significantly lowers logistics costs and enhances supply chain efficiency. This study underscores the effectiveness of integrating quantitative techniques in facility location decisions. To further refine such analyses, future research could incorporate real-time traffic data, infrastructure availability, and environmental factors. These insights offer valuable guidance for industries seeking cost-efficient, strategically positioned processing facilities.